2015
DOI: 10.1007/s11745-015-3990-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of L‐FABP T94A and MTP I128T Polymorphisms with Hyperlipidemia in Chinese Subjects

Abstract: The purpose of this study was to evaluate the relation between the L-FABP T94A and MTP I128T polymorphisms and hyperlipidemia in Chinese subjects. We recruited 390 volunteers: 201 hyperlipidemic and 189 healthy volunteers. The L-FABP T94A and MTP I128T polymorphisms were genotyped using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Anthropometry, lipid profile, and liver function of the subjects were determined. We observed that male carriers of the L-FABP A94 allele had signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
1
7
1
Order By: Relevance
“…Further, a highly prevalent human L-FABP SNP (26-38% allele frequency) [66-72] resulting in L-FABP T94A substitution alters uptake/metabolism of another branched-chain lipid, cholesterol [29,67,71,73]. Human subjects expressing the L-FABP T94A variant exhibit marked triglyceride accumulation in liver [29,71], elevated triglyceride and LDL cholesterol in serum [67,74,75], and increased incidence of cardiovascular disease [67,69,74]. Although less prevalent, a mutation in the human SCP-x gene completely abolishes SCP-x activity, markedly elevates serum levels of branched chain fatty acids (phytanic acid, pristanic acid), and induces neurodegeneration [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Further, a highly prevalent human L-FABP SNP (26-38% allele frequency) [66-72] resulting in L-FABP T94A substitution alters uptake/metabolism of another branched-chain lipid, cholesterol [29,67,71,73]. Human subjects expressing the L-FABP T94A variant exhibit marked triglyceride accumulation in liver [29,71], elevated triglyceride and LDL cholesterol in serum [67,74,75], and increased incidence of cardiovascular disease [67,69,74]. Although less prevalent, a mutation in the human SCP-x gene completely abolishes SCP-x activity, markedly elevates serum levels of branched chain fatty acids (phytanic acid, pristanic acid), and induces neurodegeneration [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Genome wide array studies (GWAS) of NAFLD estimate a 39% heritability of liver lipid accumulation as a continuous trait after controlling for age, gender, race, and BMI (219). The highly prevalent human L-FABP T94A variant (175177, 195198) is associated with TAG accumulation in liver (NAFLD) (176), primary hepatocytes (63), and serum (174, 175, 224). Hepatic levels of endocannabinoids and/or receptors (CB1 and/or CB2) of the endocannabinoid system are elevated in NAFLD (101103), alcoholic liver disease (AFLD) (102, 104), high-fat diet-induced obesity (102, 104), and in response to cannabis with CB1 agonists (e.g.…”
Section: Fabp1 In Human Health: Impact Of the Human Fabp1 T94a Variantmentioning
confidence: 99%
“…An explanation for these characteristics was that the T94A variant resulted in a total loss of function (39). Others observed no change in ligand binding specificity or changes in the affinity for binding fibrates (14), steric acid or oleic acid (15) between the wild type and the T94A variant protein. Slight changes were seen in the secondary structure binding affinities between the T94A protein and palmitic or linoleic acid (15) and differences in cholesterol affinity and uptake (16).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the T94A substitution was thought to completely abolish the binding and function properties of the protein. Recent studies revealed the substitution did not alter ligand binding affinity, however, it significantly altered conformational and functional response to fibrates as well as stability (14). The altered function was also demonstrated with fatty acids and triglyceride intermediates (15).…”
mentioning
confidence: 98%